Investigating L2 learners’ sociopragmatic development in online asynchronous discussion - Wong, Shin Pyng * (2012)
Despite a burgeoning research of pragmatics in second language learning, there has been insufficient work on the relations among social variables and speech acts in an online learning context. This study examines the sociopragmatic development of L2 learners through online asynchronous discussion. Participants were 18 undergraduate students who enrolled in a compulsory English course. The subjects took part in a web-based collaborative discussion for four weeks. In the form of computer-mediated discourse, the learners’ speech acts were analysed statistically. Social variables which are gender and familiarity between participants were identified and discussed. The descriptive findings indicate that social variables were related to certain online speech acts. Regression analysis however shows that gender and familiarity were not significant predictors of L2 learners’ online utterances. It was found that more proficient L2 learners assisted less proficient peers through active participation and employment of myriad speech acts. Results also suggest that the use of specific utterances affects a learner’s role in the organisational hierarchy of online discussion. This study suggests pedagogical implications for the L2 learners’ acquisition of sociopragmatic competence through online peer collaboration.